PHATIC SPEECH ACTS OF ENGLISH-SPEAKING INDONESIAN STUDENTS - Dian Anggraini; Yuli Widiana (Universitas Katolik Widya Mandala Surabaya, 2024)
Phatic Speech Acts are communication strategy that is a characteristic of a culture. Phatic speech acts have an important role in the communication process in Indonesia as the efforts made to demonstrate social identity and maintain social rapport in society. Therefore, this research discusses the types and function of phatic speech acts found in the daily conversation of English-speaking Indonesian students. The data source for this research is English-speaking Indonesian students at Widya Mandala Surabaya Catholic University, Madiun Campus. This research data was collected by using the non-participation observation method with the recording, note- taking, and role-play techniques. The findings of this research are a classification of 11 types of phatic speech acts consisting of (1) Addressing, (2) Expressing Empathy, (3) Gossiping, (4) Complimenting, (5) Giving Remarks, (6) Advising, (7) Offering, (8) Requesting, (9) Inviting, (10) Mocking, and (11) Swearing. The functions of phatic speech acts are: (1) Expressing hospitality, (2) Showing attention, (3) Making conversation more interesting, (4) Please others, (5) Showing concern, (6) Expressing empathy (7) Showing politeness, (8) Expressing social attachment, (9) Expressing solidarity, (10) Mocking, and (11) Building intimacy. The phatic speech act of addressing is the type of speech act that is most frequently found. On the contrary, the phatic speech act of complimenting is rarely used. The embodiment of the phatic speech act of addressing is dominantly carried out by students in daily conversations since it reflects the cultural identity of Indonesians that is friendly and warm. The phatic speech act of complimenting is not used frequently because of its conditional in nature. The complimenting requires the speaker to have an advantage that is worthy of praise, even though the praise is not sincere. The benefit of this research is to know that in daily communication, phatic speech acts could be implemented for smooth communication.